Influence of Drying Duration of Paving Block with the 5% Fly Ash Addition on Compressive Strength (Water Binder) - Nurzal Nurzal; Taufik Taufik (LP2M - Institut Teknologi Padang, 2016)
This study was conducted to determine the effect of variations in drying time with the addition of 5% by weight of fly ash in the manufacture of paving blocks through compressive strength testing. Fly ash is derived from the combustion of coal in a steam power plant of Sijantang Sawahlunto. The increase of production of fly ash causing negative impacts on the environment, so that one of the solutions to overcome such effects is by utilizing fly ash to mix and improve the quality of the paving block (concrete blocks). The composition used to make paving block that is 100% of paving blocks (cement + sand + water) and 95% of paving blocks (cement + sand + water) plus 5% fly ash with variation drying 7, 14, 21, 28 and 35 days. The result showed paving block with 5% by weight of the composition of the fly ash has a higher compressive strength than 0% by weight of fly ash. Optimal conditions obtained on the composition 5% by weight of fly ash and drying time of 35 days. Average - average compressive strength of 23.1 MPa SNI 03-0691-1996 can be classified according to quality and to the parking lot. All the test results are included in SNI, except on drying 7 days with 0% by weight of the composition of the fly ash.